Meeting the needs of people with learning disabilities and mental health problems: a review. - Coyle D (Mental Health & Learning Disabilities Care, 2000)
People with learning disabilities are vulnerable to the same mental health problems as the general population. However services for them are less than adequate. Mental health services are often reluctant to accept them, while learning disability services tend to lack the skills and resources needed to meet their additional mental health needs. Inadequacy of diagnostic and assessment processes too may hamper the provision of appropriate treatment. David Coyle reviews the needs and service provision for this neglected and challenging group, and the role of the learning disability nurse.